Relative adrenal insufficiency is a risk factor and endotype of sepsis - A proof-of-concept study to support a precision medicine approach to guide glucocorticoid therapy for sepsis - Wu, Chia-Hua; Guo, Ling; Hao, Dan; Wang, Qian; Ye, Xiang; Ito, Misa; Huang, Bin; Mineo, Chieko; Shaul, Philip W.; Li, Xiang-An (Frontiers in Immunology, 2023)
25-60% of septic patients experience relative adrenal insufficiency (RAI) and glucocorticoid (GC) is frequently used in septic patients. However, the efficacy of GC therapy and whether GC therapy should be based on the status of RAI are highly controversial. Our poor understanding about the pathogenesis of RAI and a lack of RAI animal model present significant barriers to address these critical issues. Scavenger receptor BI (SR-BI) regulates stress-induced GC (iGC) production in response to stress. We generated SF1CreSR-BIfl/fl mice and utilized the mice as a RAI model to elucidate the pathogenesis of RAI and GC therapy in sepsis. SF1CreSR-BIfl/fl mice did not express SR-BI in adrenal gland and lacked iGC production upon ACTH stimulation, thus, they are RAI. RAI mice were susceptible to cecal ligation and puncture (CLP)-induced sepsis (6.7% survival in SF1CreSR-BIfl/fl mice versus 86.4% in SR-BIfl/fl mice; p = 0.0001). Compared to a well-controlled systemic inflammatory response in SR-BIfl/fl mice, SF1CreSR-BIfl/fl mice featured a persistent hyperinflammatory response. Supplementation of a low stress dose of GC to SF1CreSR-BIfl/fl mice kept the inflammatory response under control and rescued the mice. However, SR-BIfl/fl mice receiving GC treatment exhibited significantly less survival compared to SR-BIfl/fl mice without GC treatment. In conclusions, we demonstrated that RAI is a risk factor of sepsis. We further demonstrated that RAI is an endotype of sepsis, which features persistent hyperinflammatory response. We found that GC treatment benefits mice with RAI but harms mice without RAI. Our study provides a proof of concept to support a precision medicine approach for sepsis therapy – selectively applying GC therapy for a subgroup of patients with RAI.